Enantioselective syntheses of both enantiomers of 9′-dehydroxyimperanene and 7, 8-dihydro-9′-dehydroxyimperanene and the comparison of biological activity between 9-norlignans and dihydroguaiaretic acids. Issue 13 (1st July 2016) - Yamauchi, Satoshi; Tanimura, Ryosuke; Nishiwaki, Hisashi; Nishi, Kosuke; Sugahara, Takuya; Maruyama, Masafumi; Ano, Yoshitaka; Akiyama, Koichi; Kishida, Taro
Graphical abstract: Abstract: To estimate the effect of methyl group of dihydroguaiaretic acid, which shows many kinds of biological activities, on biological activity, both enantiomers of 9′-dehydroxyimperanene (5, 6 ) and 7, 8-dihydro-9′-dehydroxyimperanene (7, 8 ) lacking one of the methyl groups of dihydroguaiaretic acid were synthesized. ( S )-7, 8-Dihydro-9′-dehydroxyimperanene (7 ) showed 4–6-fold higher cytotoxic activity than all stereoisomers of dihydroguaiaretic acid (2 –4 ). The IC50 values of ( S )-7, 8-dihydro-9′-dehydroxyimperanene (7 ) against HL-60 and HeLa cells were 6.1 μM and 5.6 μM, respectively. Though only one of three stereoisomers of dihydroguaiaretic acid showed antibacterial activity against a gram negative bacterium, both enantiomers of5 –8 showed antibacterial activity against a gram negative bacterium. This is a Letter on biological activity of 9-norlignan, in which one of methyl groups of lignan is absent.